Looking Beyond Schools: Analyzing Private Tuition in Schools in the Context of West Bengal - Sengupta, Indrani (Voices of Teachers and Teacher Educators, 2020)
There is an increasing growth of the informal education market in school education of which private tuition is one form and this relatively has garnered less attention in research in India. Private tuitions pose a threat to the idea of ‘education for all’ as mandated by RTE (2009) because it privileges the ones who can afford it at the cost of others. By taking the case of West Bengal, the paper establishes how private tuitions have a variety of implications and effects on society. This includes affecting the school system, the family dynamics and then also creating social unrest among different sections of the society. It has been found that across districts of West Bengal there is variation in terms of percentage of students going for tuition that indicates variation in the determinants of demand. As schools and private tuitions are interdependent, what a child learns in tuitions affect school outcomes particularly because school teachers are also found to be part of this market. Section 28E of RTE (2009) prohibits school teachers from providing private tuition and it needs to be implemented to increase accountability of school teachers, which would partly solve the problem of increasing reliance on private tuition.